Effect of the preparation conditions on the properties of Fe-Pt nanoparticles produced by sonoelectrodeposition - Nguyen, Hoang Luong (H. : ĐHQGHN, 2017)
Fe-Pt materials have been widely prepared by vacuum evaporation technique. Recently, chemical and physicochemical methods have been successfully used to make Fe-Pt nanoparticles, thin films. This paper reported another physicochemical method, namely sonoelectrodeposition, to produce Fe-Pt nanoparticles. In the sonoelectrodeposition, the electrodeposition process was assisted with a sonicator. The Ti horn of the sonicator played a role as the cathode on which Fe-Pt nanoparticles were deposited. After a certain time of deposition, a sonic pulse was applied to remove the particles from the Ti cathode. The composition of Fe-Pt particles can be controlled by changing the concentration of Fe and Pt ions in the electrolyte and the deposition voltage. The particle size can be adjusted by the time of deposition. The as-deposited Fe-Pt nanoparticles were ferromagnetic at room temperature. Upon annealing at 700°C for 1 h under H2 atmosphere, the saturation magnetization and the coercivity of the nanoparticles were improved significantly. Sonoelectrodeposition is a promising technique to make large quantity of Fe-Pt nanoparticles.